Proposta de processo decisório para reabilitação das áreas de disposição final de resíduos sólidos urbanos na região metropolitana de Goiânia - Melo, Diógenes Aires de (2017)
One of the biggest concerns with municipal solid wastes (MSW) is the risk of degradation of final disposal areas (FDA), since many landfills installed as sanitaries, in Goiás State, Brazil, returned to the condition of ilegal dump sites (MP-GO, 2012), and because the technical standards don´t adopt the newest concept of environmental geotechnics (JUCÁ, 2003). It´s necessary evaluate the FDA of MSW and establish the prioritization criterias for the rehabilitation in order to decide about their future. The research aimed the proposition of a multicriteria decision process for the rehabilitation of FDA of MSW in the Metropolitan Region of Goiânia (MRG). The MRG, composed by 20 municipalities, was choosen because it´s responsible for the generation of 46.85 % of the total of 4,088.23 tonnes/day of MSW of Goias State (SECIMA, 2014b). Three evaluations were carried out in 20 areas: quality evaluation of final disposal, through Landfill Quality Index (LQI) (FARIA, 2002); evaluation of environmental vulnerability, with the elaboration of synthesis map, integrating Topograpic Wetness Index (TWI), Length Slope (LS), Water Table and Soils; and the evaluation of legal restriction of the area uses according with Resolution No 5/2014 of Environmental State Council. The evaluations showed only 4 FDA of Aparecida de Goiânia, Bela Vista de Goiás, Trindade and Senador Canedo Counties obtained LQI greater than 8.01 and they were considered as a sanitary landfills. Most areas has moderate vulnerability and the other areas range between low and very low. Only 4 areas are free of legal restriction of use: Inhumas, Bonfinópolis, Bela Vista de Goiás and Hidrolândia; 2 are subject to agreement: Santo Antônio de Goiás and Brazabrantes; and the other 14 are restricted areas. From the hierarchical structure of the 3 combined and weighted evaluation criteria for each of the 20 alternative-areas, the Analytic Hierarchy Process (AHP) was performed, which ordered Guapo as the most priority and lastly, Hydrolandia County. The decision about the future of each area indicates in ascending order that the following 14 FDA: Guapó, Caldazinha, Nova Veneza, Caturaí, Nerópolis, Aparecida de Goiânia, Trindade, Senador Canedo, Goianira, Goianápolis, Terezópolis de Goiás, Aragoiânia, Abadia de Goiás e Goiânia, should to be closed and recovered. On the other hand, the FDA´s of Santo Antônio de Goiás, Brazabrantes, Inhumas, Bonfinópolis and Hidrolândia may continue to dispose their wastes since the elaboration and approval of sanitary landfill projects, as determined by the respective Environmental Agency. The FDA of Bela Vista de Goiás will be able to continue as a sanitary landfill. Finally, possible scenarios were indicated for the final disposal future of the MSW of MRG by sending preferably to the 4 shared landfills pointed by the Solid Waste State Plan, private landfill or manual trench landfill for counties with the generation less than 10 tonnes/day, together with the search of new solutions for final destination. It was concluded that not all landfill considered sanitary can continue its activities due to the environmental fragility of the area and non-compliance with the restrictions imposed by the legislation.